2008
DOI: 10.1116/1.2949232
|View full text |Cite
|
Sign up to set email alerts
|

Magnetron sputtered Si–B–C–N films with high oxidation resistance and thermal stability in air at temperatures above 1500 °C

Abstract: Novel quaternary Si-B-C-N materials are becoming increasingly attractive because of their possible high-temperature and harsh-environment applications. In the present work, amorphous Si-B-C-N films were deposited on Si and SiC substrates by reactive dc magnetron cosputtering using a single C-Si-B or B 4 C -Si target in nitrogen-argon gas mixtures. A fixed 75% Si fraction in the target erosion areas, a rf induced negative substrate bias voltage of −100 V, a substrate temperature of 350°C, and a total pressure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The ceramic sample CS2H1900 shows little mass change up to 1500 ℃, indicating a great oxidation resistance in such conditions. After oxidized at 1200 ℃ in dry air for 5 h or 85 h, the oxidation layer on the ceramic surface is coarse, and has lots of cracks on its surface [70]. The layer has a thickness of about 5-10 µm, and mainly contains crystalline SiO 2 , with a small content of nitrogen and carbon, and little content of boron.…”
Section: Oxidation Resistance Of the Si-b-c-n Ceramicmentioning
confidence: 99%
See 1 more Smart Citation
“…The ceramic sample CS2H1900 shows little mass change up to 1500 ℃, indicating a great oxidation resistance in such conditions. After oxidized at 1200 ℃ in dry air for 5 h or 85 h, the oxidation layer on the ceramic surface is coarse, and has lots of cracks on its surface [70]. The layer has a thickness of about 5-10 µm, and mainly contains crystalline SiO 2 , with a small content of nitrogen and carbon, and little content of boron.…”
Section: Oxidation Resistance Of the Si-b-c-n Ceramicmentioning
confidence: 99%
“…It is also found that when the nitrogen content is higher than 30%, the electrical resistivity may be much larger Fig. 21 Thermogravimetric curve of CS2H1900 and CD2H1900 ceramics in an air flow with a heating rate of 10 ℃/min [70].…”
Section: Electrical and Optical Properties Of Thementioning
confidence: 99%
“…Subsequently, Si and more than likely B are oxidized forming a protective borosilicate matrix 13 . It has been shown that above 1100 °C, B 2 O 3 reacts with SiO 2 forming protective borosilicate glass that fills the pores in the amorphous SiO 2 structure 39 resulting in a dense amorphous SiO x -based matrix as shown in Fig. 3(a).…”
Section: Resultsmentioning
confidence: 99%
“…Multi-component films in the Si-B-C-N system are considered as a new generation of hard coatings for various technical applications. Recently, it has been reported that the Si-C-N-ceramics doped with boron exhibited great increase in high-temperature stability and oxidation resistance [6][7][8][9]. These effects are possibly explained by production of turbostratic BN phase [10] and integration of carbon in B-C-N zones [11].…”
Section: Introductionmentioning
confidence: 99%
“…Si-B-C-N films have been deposited by different methods including dc magnetron [6,8,11] and pulsed magnetron [9,13] sputtering, ion beam assisted sputter deposition [7], electron-cyclotron resonance microwave plasma assisted vapor deposition [15]. In Refs [8,13], the Si-B-C-N films have been deposited by sputtering of the target composed of B 4 C plate overlapped by Si stripes (25 % B 4 C + 75 % Si) in the argon-nitrogen gas mixture (50 or 75 % Ar fraction).…”
Section: Introductionmentioning
confidence: 99%